ECONOMICS ANALYSIS OF THE MOST IMPORTANT INFLUENCING INVESTMENT ALLOCATIONS FOR AGRICULTURAL RECLAMATION IN IRAQ FOR THE PERIOD (1990- 2010). - SHUKR , ALI S.; ALI, Eskander H. (Diyala Agricultural Sciences Journal, 2013)
Investment business positive economic consequent increase in fixed capital and operating the basis of considering the problem of salinity is one of the most important problems facing Iraqi agriculture, which leads to low productivity per unit area, which in turn led to the lower contribution of agricultural output of GNP as was the reason for exit area wide range of land-scale agriculture, economic, so the aim of research is to conduct an economic analysis of investment in land reclamation in Iraq for the period (2010 -1990), and review the reality of reclamation within this period show that the average areas reclaimed amounted to 275214.6 donum and the largest area reclaimed was in 2002, and through the annual growth rates show that the rate of growth during the period( 1990 - 2010)) which is half the duration of the study was positive, but the second period was the growth rate which is negative due to the continuing decline in allocations to invest in this area, as it turns out that the highest percentage contribution to the output of the agricultural of GDP was 26.9% during 1991 either lower the contribution rate in 2010 was at 7.2%. In order to identify the most important factors affecting the investment allocations for reclamation projects agriculture was estimated function of investment that show the relationship between investment allocations as the dependent variable and all of the GDP at constant prices and agricultural output in constant prices and area reclaimed donums explanatory variables and using the method of least squares OLS found that the linear function was the appropriate functions to be used expression of the relationship to overcome the of economic and statistical and econometrical tests standard and GDP was the most influence and determine the amounts allocated for investment as the change by one unit of the investment allocations will change by 147.9 with the survival of other factors constant at averages, and was able to variables explanatory explain 67% of the fluctuations in the depended v. F-test also showed significant model as all.